Answer:
2.4
Step-by-step explanation:
let a = vol in the 1st tank (in liters)
let b = vol in the 2nd tank
:
"Two fish tanks contained 9L of water altogether."
a + b = 9
:
" 60% of the water was scooped out from the first tank"
a - .6a = .4a amt in the 1st tank now
:
" and 0.6L of the water was scooped out of the 2nd tank."
a - .6 = amt in the 2nd tank
:
" At the end both fish tanks had the same amount of water. "
.4a = b - .6
.4a - b = -.6
use elimination with the first equation
.4a - b = -.6
a + b = 9
-----------------addition eliminates b, find a
1.4a + 0 = 8.4
a = 8.4/1.4
a = 6 liters in the 1st tank
then, obviously,
9 - 6 = 3 liters in the 2nd
:
:
Confirm this in the 2nd statement
" 0.6L of the water was scooped out of the 2nd tank. At the end both fish tanks had the same amount of water. "
.4(6) = 3 - .6
2.4 = 2.4